PERMAINAN BAHASA SEBAGAI MEDIA LITERASI EDUKASI SISWA KELAS VI SDN MUKTIHARJO KIDUL 03 - Niwi Sruti Handayani; Ida Dwijayanti; Sumarno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to determine the role of using language games as a speaking medium by class VI students at SDN Muktiharjo Kidul 03. This research involved class VI students at elementary schools in Semarang City. This research is quantitative research where the sample was selected purposively. The research subjects were 6th grade students at SD Negeri Muktiharjo Kidul 03. Researchers used their own research instruments with the help of observation and test guidelines. Research procedures are used by means of preparation, observation, determining the type of game, and developing a research plan flow. Language game activities used in learning Indonesian include games for selecting story texts, games for composing paragraphs, and chain stories. The research results show that the abilities of class VI students at SDN Muktiharjo Kidul 03 can be improved through the application of educational literacy games. Students become more active, confident, enthusiastic and motivated.